Avon : - Klepacki, Laura (John Wiley & Sons, 2005)
AVON: Building the World's Premier Company for Women is the first book ever to show how this cosmetics juggernaut achieved such incredible success, while revealing secrets any business can use to effectively market products of all kinds-especially to women. Avon, the Winning Formula for Selling to Women Around the World, has come a long way since handing out its first perfume sample back in 1886. The company, long famous for ringing customer doorbells, is now the world's largest direct sales organization-with almost five million representatives in more than 140 countries.